A transcriptome atlas and interactive analysis platform for autoimmune disease. (27th June 2022) - Shen, Zhuoqiao; Fang, Minghao; Sun, Wujianan; Tang, Meifang; Liu, Nianping; Zhu, Lin; Liu, Qian; Li, Bin; Sun, Ruoming; Shi, Yu; Guo, Chuang; Lin, Jun; et al.
Abstract: With the rapid development of next-generation sequencing technology, many laboratories have produced a large amount of single-cell transcriptome data of blood and tissue samples from patients with autoimmune diseases, which enables in-depth studies of the relationship between gene transcription and autoimmune diseases. However, there is still a lack of a database that integrates the large amount of autoimmune disease transcriptome sequencing data and conducts effective analysis. In this study, we developed a user-friendly web database tool, Interactive Analysis and Atlas for Autoimmune disease (IAAA), which integrates bulk RNA-seq data of 929 samples of 10 autoimmune diseases and single-cell RNA-seq data of 783 203 cells in 96 samples of 6 autoimmune diseases. IAAA also provides customizable analysis modules, including gene expression, difference, correlation, similar gene detection and cell–cell interaction, and can display results in three formats (plot, table and pdf) through custom parameters. IAAA provides valuable data resources for researchers studying autoimmune diseases and helps users deeply explore the potential value of the current transcriptome data. IAAA is available. Database URL : http://galaxy.ustc.edu.cn/IAAA